Perceived Services and Reported Opinions about Self-Care during Pregnancy and Lactation by Community Pharmacists: A Cross Sectional Study - S. SHIROMWAR, SHRUTI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study was planned to evaluate the community pharmacists’ services regarding self-care during pregnancy and lactating women in the Northern Border Region of Saudi Arabia. Methods: A cross-sectional questionnaire-based survey was performed among the community pharmacists in the Northern Border Region of Saudi Arabia consists of randomly elected 156 pharmacies. The study purpose briefly described face-to-face to the pharmacist on duty to fill self-care questionnaire regarding services and opinions intended for pregnant and breastfeeding women. Results: Pharmacists specified that they have sufficient knowledge to offer advice (47.82%) and to solve medication and health-related problems (39.13%) during pregnancy and lactation. The confidence level of pharmacists to give drug-related opinion and counseling to patients was 69.56% and 39.13% respectively. All the participated pharmacists’ want continuing education program and 47.82% of pharmacist advised pharmacy school training on this issue to improve/update the knowledge on the issue. Conclusion: Pharmacists have different opinions regarding pregnancy and breastfeeding associated illness and also highlighted the need for interventions, including continuing professional development and revision of the undergraduate pharmacy curriculum.